Diastereodivergent organocatalysis for the asymmetric synthesis of chiral annulated furans1. Issue 7 (15th July 2015) - Verrier, Charlie; Melchiorre, Paolo
<x xml:space="preserve">Abstract</x> Stereoselective methods to prepare chiral annulated furans are reported. Complementary organocatalytic systems ensure access to all possible stereoisomeric products.